2004
DOI: 10.1007/s00586-003-0617-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of intramuscular pressure and surface electromyography of the multifidus muscle

Abstract: The anatomic proof of a spinal compartment and the clinical symptoms of compartment syndrome in patients with chronic back pain are inconsistent with the rarely met measuring criteria of intramuscular pressure (IMP). Previous studies assume a dependence of the IMP on spinal alignment (degree of lumbar spine flexion) and the degree of muscle activation. The significance of these disturbance variables in the interpretation of IMP could explain the above discrepancy. This study therefore investigates the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, ours is the first study of intramuscular pressure after surgery. Lumbar intramuscular pressure at rest in healthy human adults in the prone position is 8.3-10 mm Hg, 12,13,20 in the lateral decubitus position it is 16 mm Hg, 12 and in the supine position it is 18 mm Hg. 12 In this prospective study, intramuscular pressure did not differ significantly between the 2 procedures, not only when measured with patients in the supine position but also when measured with patients in the lateral decubitus position.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To the best of our knowledge, ours is the first study of intramuscular pressure after surgery. Lumbar intramuscular pressure at rest in healthy human adults in the prone position is 8.3-10 mm Hg, 12,13,20 in the lateral decubitus position it is 16 mm Hg, 12 and in the supine position it is 18 mm Hg. 12 In this prospective study, intramuscular pressure did not differ significantly between the 2 procedures, not only when measured with patients in the supine position but also when measured with patients in the lateral decubitus position.…”
Section: Discussionmentioning
confidence: 95%
“…12, 13 Kobayashi et al reported that, in a rat model, increasing the intramuscular pressure in paraspinal muscles decreased intramuscular blood flow and increased expression of neuropeptide in the dorsal root ganglion, thereby causing low-back pain.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies showing the influences of diabetic neuropathy and/or angiopathy on the outcomes of lumbar spine surgery [13][14][15] . However, for the impact of diabetes on patients undergoing CSM, there have been limited number of studies reporting this, and their results remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the diabetic neuropathy and/or angiopathy have negative effects on the outcomes of lumbar spine surgery [13][14][15] .…”
mentioning
confidence: 99%
“…36,37 Exploring these regions using measurement of intramuscular pressure with specialized probes may also be feasible. 38,39 Shah et al 40,41 developed a technique for measuring the local biochemical milieu of skeletal muscle to determine the presence of inflammatory mediators in trapezius muscle trigger points, and this Abbreviations: AbP, abnormal-to-palpation; ES1, erector spinae muscles adjacent to NP1; ES2, erector spinae muscles adjacent to NP2; ESA, erector spinae muscles adjacent to AbP; MVIC, mean voluntary isometric contractions; NP1, normal to palpation, above AbP site; NP2, normal to palpation, below AbP site.…”
Section: Commentmentioning
confidence: 99%